PENGARUH FINANCIAL STABILITY, EXTERNAL PRESSURE, NATURE OF INDUSTRY DAN RATIONALIZATION TERHADAP FINANCIAL STATEMENT FRAUD DALAM SUDUT PANDANG FRAUD TRIANGLE PADA PERUSAHAAN SEKTOR REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - Anom Ayu Megawati Lestari; I Putu Nuratama (UNHI Press, 2020)
Financial Statement Fraud is the negligence or deliberate misrepresentation in financial reporting in order to commit fraud to users of financial statements. Where researchers want to know the effect of financial stability, external pressure, nature of industry and rationalization on financial statement fraud in the perspective of the fraud triangle. This research was conducted at Real Estate and Property Sector companies listed on the Indonesia Stock Exchange in 2014- 2017. The sample used was a number of 31 companies during 4 years of research, with a purposive sampling method. The analysis technique used is multiple regression test. Based on the results of the multiple regression test analysis, it was found that the variables of financial stability and external pressure had no effect on financial statement fraud. While the variable nature of industry and rationalization have a negative and significant effect on financial statement fraud.